Transformasi Metode Karyawisata: Dari Observasi ke Refleksi dalam Pembelajaran Modern - Ningsih, Titik Widiyah; Affandy, Ali Nuke; Hermoyo, R. Panji (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
The transformation of the field trip method from mere observation to reflection in modern learning reflects efforts to integrate direct experience with critical thinking to support the achievement of more meaningful learning outcomes. This article discusses the paradigm shift in the implementation of field trips, which previously only focused on observation in the field, towards an approach that involves an experience-based reflective process. In the context of 21st century education, this method is integrated with interactive technology and project-based learning strategies, allowing students to explore, analyse, and connect theoretical knowledge with practical applications holistically. This study shows that a reflective approach improves students' conceptual understanding, critical thinking skills, and emotional engagement. Thus, the transformation of this field trip method not only revolutionizes the way learning is carried out but also prepares students to become independent learners who are ready to face the challenges of the modern world. The results of this research can be the basis for the development of education policies that are more adaptive to the needs of students in the digital era.